EXPENDITURE ON OIL PALM FARMERS’ HOUSEHOLDS IN BAYUNG LENCIR SUBDISTRICT MUSI BANYUASIN REGENCY - Khosy Khoirunnisa; Riswani Riswani; Lifianthi Lifianthi (BIOVALENTIA: Biological Research Journal, 2023)
The profitable business potential of palm oil entices the community and the Indonesian Government to develop it. It makes palm oil farming as a major source of farmers’ livelihood. However. oil palm plantations confront a number of challenges. including unstable prices and production. This will affect the household income obtained by farmers. The aim of this research is to examine the characteristics of oil palm farming. such as production costs. revenues and income as well as the proportion of household expenditure devoted to food and non-food consumption. This study was carried out in Bayung Lencir District. Musi Banyuasin Regency. South Sumatra Province. The disproportionate random sampling was used to acquire data from 90 respondents who are independent oil palm farmers. The depth interview method was used to acquired data. According to the findings. oil palm farmers’ income was IDR. 122,143,547/cultivation area/year or IDR. 10,178,629/cultivation area/month. The annual household income of oil palm farmers derived form on farm income other than oil palm, off farm income and non-farm income. The proportion of household expenditure for food consumption was 26.30%. while the proportion for non-food consumption was 73.70% and indicating that oil palm farming households are classified as prosperous since there is IDR. 1.015.871/month to be saved.